Perancangan Sistem Audio Crossover Berbasis Digital Filter Menggunakan STM32L4 - Mohammad Dicky Nasrulloh (Jurnal Jaringan Telekomunikasi, 2019)
Analog telecommunication system equipment is now starting to develop and be replaced with digital telecommunication systems, one of them is in the audio signal processing. The focus of audio processing is audio crossover. Audio crossover in development there are still many who use analog systems. This analog system has disadvantages when adjusting the sound balance because it still uses analog filters to balance it. It is necessary to develop a technology that aims to create a digital-based crossover audio system using the STM32L4, so that by using this digital-based signal processing it is able to adjust the sound more specifically than the signal processing used analog based. This digital filter uses the Finite Impulse Response (FIR) method. Testing audio crossover using STM32L4 produces a digital-based crossover audio system design using a STM32L4 microcontroller with a voltage of 3.3V as power supply, mp3 player as sound input device, FIR filter as digital filter processing, LM386 as sound amplifier and speaker as sound output for crossover audio on rangelow frequency (200Hz to 4000Hz), high (2200Hz to 6000Hz), medium (200Hz to 4000Hz).